1980
DOI: 10.1007/bf02085379
|View full text |Cite
|
Sign up to set email alerts
|

The effect of internal iliac artery embolization on the prostatic gland in the dog

Abstract: Investigations were carried out on dogs in order to study the changes in the prostatic gland after embolization of the internal iliac arteries. The experiments showed that slight fine-celled infiltrations occurred in the interstitial tissue as a result of ischaemia of that organ. The authors are of the opinion that embolization of the internal iliac arteries may be used in clinical practice as a method of treating haemorrhages from the prostatic gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Similar findings of lymphocyte and fibroblast infiltrations in interstitial tissue after embolization of the internal iliac arteries have been reported (18); these authors speculated that this occurred as a result of the reaction of the organ to ischemia. In a recent study of healthy pigs (25), microscopic examination showed fibrosis and atrophy of the gland consistent with the histologic findings of the present study.…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings of lymphocyte and fibroblast infiltrations in interstitial tissue after embolization of the internal iliac arteries have been reported (18); these authors speculated that this occurred as a result of the reaction of the organ to ischemia. In a recent study of healthy pigs (25), microscopic examination showed fibrosis and atrophy of the gland consistent with the histologic findings of the present study.…”
Section: Discussionsupporting
confidence: 79%
“…Transcatheter arterial embolization (TAE) of the prostate has been proposed as an alternative treatment of BPH with an initial study demonstrating the feasibility of the technique in 2000 . Animal studies showed the efficacy of this technique in dogs with a decrease in prostate volume as well as preserved sexual desire and erectile function in pigs . Recently, there has been a renewed interest in this technique with a number of case reports and small series showing the efficacy of this technique in humans with short and mid‐term follow up.…”
mentioning
confidence: 99%
“…Several years later was published the first animal study relating to the outcomes of embolotherapy in postprostatectomy hemorrhage. The purpose of this investigation was to explore the changes in prostate gland tissue after embolization of the internal iliac arteries and justify its property in clinical practice [ 12 , 13 ]. Other two animal studies reported prostate volume reduction in response to transcatheter arterial embolization [ 14 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%